Diversity of the cyrtophorid genus Chlamydodon (Protista, Ciliophora): its systematics and geographic distribution, with taxonomic descriptions of three species. Issue 5 (4th July 2018) - Qu, Zhishuai; Li, Lifang; Lin, Xiaofeng; Stoeck, Thorsten; Pan, Hongbo; Al-Rasheid, Khaled A. S.; Song, Weibo
Abstract : The ciliate genus Chlamydodon is characterized by a unique cross-striated band (CSB) along the cell perimeter. To date, more than 15 nominal species have been assigned to this genus, all of which are exclusively from marine or brackish water. In the present work, we have revised the genus according to the available data and suggest an illustrated key to aid species diagnosis. In addition, the systematic relationships of chlamydodontid congeners were analysed based on SSU rRNA gene sequences, indicating that all congeners belong to a well-defined clade. Furthermore, we investigated three species from coastal areas of China, including two new species, Chlamydodon wilberti sp. nov. and C. bourlandi sp. nov., using morphological and phylogenetic criteria. Chlamydodon wilberti sp. nov. is characterized by a cell size of 65–105 × 35–60 µm, a complete CSB, and 38–49 somatic kineties. Chlamydodon bourlandi sp. nov. has a cell size of 150–250 × 65–150 µm, a complete CSB, a reddish to violet cell colour, 83–97 somatic kineties, and 40–68 contractile vacuoles. As a further contribution, a well-studied species, C. triquetrus (Müller, 1786) Kahl, 1931, is also re-described. www.zoobank.org/urn:lsid:zoobank.org:pub:B83A5466-9D2B-4502-9A23-F16A61D48172 .